The Testament of García Fernández (1241): an Example of the Conception of the Death of the Castilian Nobility in the Thirteenth Century (Edad Media. Revista de Historia, 2024)
This essay studies the mentality of the aristocracy regarding death of the privileged estates, especially nobility, and the management and the distribution of their possessions through the study of the testament of García Fernández, High Steward of king Ferdinand III and tutor of Alfonso X. To achieve this, a diplomatic study of this type of documents will be conducted, comparing it with other examples of the Castilian aristocracy, as well as reviewing the current state of research on this issue.  The study will conclude with an analysis of the provisions contained inthe testament of García Fernández, whose figure will be also examined. We can conclude that the people who were part of the Castilian stately regime of the 13th century made great economic and spiritual efforts for the salvation of their soul. Furthermore, because the will being studied is not anoriginal, but a 16th century copy, its documental tradition will be carefully examined.
Keywords: mentality; castilian nobility; testament; donations; attitude to death